Aeroelastic flutter performance of shape memory alloy embedded 3D woven composite plate under subsonic flow - Baitab, Danish Mahmood (2021)
Recent advancements in the aeroelasticity of aircraft structures show an increasing trend in using smart materials with composite structures for improved aeroelastic performance. An example is using shape memory alloys (SMAs) to be combined with composite structures either as actuators or for morphing capabilities. SMA has the ability to accommodate strain rather than breakage by unfolding its lattice when a load is applied and also, it generates stresses due to phase transformation from martensite to austenite at higher temperatures. Due to this coupling effect of SMAs in response to load and temperature, SMAs are embedded in laminated composites for improving damping, stiffness and vibrational characteristics. However, SMA embedded laminated composites are poor in through-the-thickness mechanical properties and SMA-induced stresses and temperature can cause delamination of plies that ultimately results in structural failures under high vibrations. In this research, SMA wires are embedded in the glass-fibre reinforced composites using 3D woven reinforcements to improve tensile and vibrational characteristics. 3D woven reinforcements provides delamination resistance, higher through-the-thickness mechanical properties and a strong grip to SMA wire due to binding yarns of 3D structure in through-the-thickness direction. Three different 3D woven orthogonal interlock configurations having different interlocking pattern of yarns with SMA wire are analysed in terms of tensile, dynamic and aeroelastic flutter properties. These 3D configurations are layer-to-layer (L2L), through-the-thickness (TT), and a modified interlock (MF) structure that provides the strongest grip to SMA wire than L2L and TT. SMA positioning was also evaluated for both dynamic and aeroelastic flutter properties i.e. SMA at mid, near to trailing, and near to leading edge of cantilevered composite plate. Tensile results showed that embedding SMA wires into structures have significantly improved tensile properties due to the coupling effect of SMA. The vibrational characteristics are also improved by embedding SMA wire and SMA wire at mid has a higher impact on bending mode frequencies while torsional mode frequencies are more affected for SMA wire at near to trailing and leading edge. Interesting results are obtained from aeroelastic testing by wind tunnel test. Activating SMA results in decrement of flutter speed and flutter frequency due to increment in flexibility of the deflected plate in airflow by SMA-induced stresses. However, there is an improvement in post-flutter behavior as the bending and twist limit cycle oscillation (LCO) amplitudes are reduced by activating SMA wire. Among 3D configurations, L2L displayed the highest increase of 34.9% in Young’s modulus as L2L provides more freedom to SMA for generating stresses due to loose grip of yarns to SMA. For dynamic properties, L2L with SMA at mid showed the highest percentage increment of 17%, 11% and 4% in natural frequencies of first three bending modes respectively. For post-flutter behavior, L2L with SMA near to trailing edge showed a significant decrement of 22.2% in twist LCO amplitude while L2L with SMA at mid showed a decrement of 9.5% for bending LCO amplitude. Hence, this work showed that embedding SMA is beneficial for improving tensile and dynamic properties as well as mitigating the post-flutter vibrations but as the consequence of reduced flutter speed and frequency.